916. Increased efficiency and impact of implementing ILUM insight within an antimicrobial stewardship program (ASP) at an academic medical center. (15th December 2022) - Shields, Ryan K; Marini, Rachel V; Shah, Sunish; Falcione, Bonnie A; Potoski, Brian A; Liu, Leanna; Goshorn, Eli S; Clarke, Lloyd; Viehman, Alex; Hadi, Christiane; Kwak, Eun Jeong; Samanta, Palash; et al.
Abstract: Background: An ASP is mandated for all hospitals and requires extensive resources with multidisciplinary collaboration. We measured the impact of implementing real-time decision support software (ILUM Insight) within our ASP. Methods: Our ASP has relied on prior authorization since 2002 and focused audit and feedback since 2015. In August 2021 we implemented to bring actionable data to front-line stewards. ILUM provides real-time notifications, organizes communications, and tracks patient-and provider-level data. We hypothesized that ILUM would increase the efficiency of ASP workflow and result in decreased antimicrobial utilization. We compared data 6 months before (8/20 – 1/21) and after (8/21 – 1/22) implementation. There were no significant staffing changes during either period. Results: Existing notifications within ILUM were tailored to local practices, including alerts with intervention for positive blood cultures, antibiotic de-escalation, and bug-drug mismatches. New notifications were built for restricted antimicrobials, antibiotic timeouts, and MRSA screening. ASP pharmacists and physicians received training in July and November, respectively. A breakdown of all notifications received during the post-implementation period is provided in Fig 1. With increased ILUM usage, the number of interventions made by our ASP increased while missed opportunities decreased (Fig 2. ). During the same time period, ASP communications rose from 205 to 1200 per month. Comparing pre- and post-implementation periods, antimicrobial days of therapy (DOT) per 1, 000 patient days (PD) decreased by 14.5% from a median of 969 to 846 per month (Fig 3; P =0.002). Antimicrobial expenditures were decreased by a median 21% per month during the post-intervention period compared to baseline. Among patients prescribed antimicrobials during an index admission, 30-day re-admissions decreased from 330 to 262 and re-admissions associated with re-ordering of antimicrobials decreased from 235 to 182 (Fig 4 ). Conclusion: Custom-designed, task-specific software improves the efficiency of daily ASP workflow and significantly decreased antimicrobial utilization without the need for additional ASP team members. Disclosures: Ryan K. Shields, PharmD, MS, Infectious Disease Connect: Advisor/Consultant|Merck: Advisor/Consultant|Merck: Grant/Research Support|Roche: Grant/Research Support J Ryan Bariola, MD, Infectious Disease Connect: Salary support|Merck: Grant/Research Support Caley Yakemowicz, n/a, Infectious Disease Connect: Employee Courtney Simonick, n/a, Infectious Disease Connect: Stocks/Bonds Riaan Erwee, na, Infectious Disease Connect: Employee Erin K. McCreary, PharmD, Infectious Disease Connect: Advisor/Consultant Rima Abdel-Massih, MD, Infectious Disease Connect: Co founder and Chief Medical Officer|Infectious Disease Connect: Ownership Interest.